Production systems and energy potential of tidal energy - Quintero-González, Julián Rodrigo; Quintero-González, Laura Estefanía (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
This article discusses the concept of tidal power and distinguishes the types of systems to exploitation the tidal energy; the same way; it also shows how this technology serves as a source of energy in some countries around the world, which is a role associated with the energy potential available in each region. This point equally shows through numbers in GWh/year per km2 reservoir surface. Last but not least, it is the influence that this technology has had on the environment, its contributions for improving and evaluating from an environmental point of view.